Pembentukan Perilaku Moral di SDN Gayungan II/423 Surabaya - Fioren Juni Kurnia Putri; Apri Irianto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to describe the formation of moral behavior and the obstacles faced in the formation of moral behavior at SDN Gayungan II/423 Surabaya. The approach used in this research is a qualitative approach, with a descriptive qualitative research type. Data collection techniques used include interviews with school principals, teachers and students as well as observation and document analysis. The results of the research show that the formation of moral behavior at SDN Gayungan II/423 Surabaya is carried out through school programs (Program Sekolahe Arek Suroboyo), learning in the classroom, and routine activities (5S activities, reading Asmaul Husna, singing Indonesia Raya songs, praying together, activities I can, Friday clean the environment, ant movement, memorize short letters of the Qur'an, congregational prayers, and remo dance). Obstacles or obstacles in the formation of moral behavior at SDN Gayungan II/423 Surabaya are the lack of reinforcement from parents, the commitment of teachers, the existence of inclusive students, understanding of student character, the mismatch between the wishes of parents and the school, as well as limited school facilities and infrastructure.